Textile designs of Japan (Japan Textile Color Design Center, 1967)
This book is supposed that nowhere in the world has richer and more varied progress been made than in Japan in the field of textiles. Underneath the whole current flows the creative spirit of the Japanese race. The pattern of thier culture is to be sought in a long succession of ceasless growth with the times, and not in any static form attached to the past. Needless to say, it has been continued down to the present days.